2013
DOI: 10.1185/03007995.2013.811403
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparative outcomes of US type 2 diabetes patients initiating analog basal insulin therapy

Abstract: Results from this real-world EMR analysis suggest that among T2DM patients, initiating insulin treatment with insulin glargine may be associated with better treatment persistence and glycemic control, with similar prevalence of hypoglycemia and weight change, compared with initiating with insulin detemir. This study is limited by the retrospective nature of the data collection using EMRs and inability to confirm accuracy and completeness of data by secondary chart review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…There is less data available for analysis of hypoglycemic risk associated with different insulins from the "real-world" setting, and recent studies from the US are limited to comparisons between insulin glargine and insulin detemir. A study of patients initiating insulin glargine or insulin detemir reported similar hypoglycemia prevalence for both insulins (3.6% vs. 4.1% [p ¼ .4338], respectively) over 1 year of follow-up 6 . In a study in which patients were switched between insulins, 1 year hypoglycemia prevalence rates of 2.0% versus 2.1% (p ¼ .889) were reported for patients switching from insulin glargine to insulin detemir or continuing with insulin glargine, respectively, and 2.3% versus 1.6% (p ¼ .2314) in patients switching from insulin detemir to insulin glargine or continuing with insulin detemir, respectively 16 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is less data available for analysis of hypoglycemic risk associated with different insulins from the "real-world" setting, and recent studies from the US are limited to comparisons between insulin glargine and insulin detemir. A study of patients initiating insulin glargine or insulin detemir reported similar hypoglycemia prevalence for both insulins (3.6% vs. 4.1% [p ¼ .4338], respectively) over 1 year of follow-up 6 . In a study in which patients were switched between insulins, 1 year hypoglycemia prevalence rates of 2.0% versus 2.1% (p ¼ .889) were reported for patients switching from insulin glargine to insulin detemir or continuing with insulin glargine, respectively, and 2.3% versus 1.6% (p ¼ .2314) in patients switching from insulin detemir to insulin glargine or continuing with insulin detemir, respectively 16 .…”
Section: Introductionmentioning
confidence: 95%
“…Thus, the most recent position statement on managing hyperglycemia from the ADA/EASD suggests that, to achieve or maintain glycated hemoglobin (A1C) targets, treatment intensification with additional oral antidiabetic drugs (OADs) or the addition of injectable therapy to OAD regimens is eventually required for many patients 4 . Recent studies have highlighted the potential benefits to patients with T2D of initiating insulin therapy early in the course of disease 5,6 ; the ADA/EASD position statement recommends the initiation of basal insulin as an option for first add-on therapy to metformin. The ADA/EASD position statement also recommends the use of basal insulin for patients in whom A1C targets are not met despite the use of up to three antihyperglycemic agents 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study of a large commercially insured insulin-na€ ıve population in the US, Ascher-Svanum et al found that only 18% of the people with T2DM who initiated insulin continued treatment in the year after initiation without any interruption or discontinuation 10 . With regards to basal insulin in particular, studies have found that approximately 55-80% of people with T2DM (identified from large commercial insurance databases) who were prescribed insulin glargine remained treatment persistent within the year after initiation [11][12][13][14] . In a separate study evaluating persistence with injectable antihyperglycemic medications among a managed care population, Cooke et al reported that 29% of patients initiating basal insulin or exenatide were persistent at 12 months after initiation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged insulin dysfunction results in the progressive development of specific complications, including retinopathy with potential blindness, nephropathy that may lead to renal failure, neuropathy with risk of foot ulcers, limb amputation and cardiovascular disease (11). In modern medicine, there are no effective curative therapies for diabetes mellitus (12). In addition, current anti-diabetic therapies, such as insulin injection and hypoglycemic agents, usually have adverse sideeffects and decreased efficacy over time (13,14).…”
Section: Introductionmentioning
confidence: 99%